Hip abduction machine is better than free weights to target the gluteus medius while minimizing tensor fascia latae activation. (April 2022) - de Almeida Paz, Isabel; Frigotto, Michele Fernandes; Cardoso, Charles Alexandre; Rabello, Rodrigo; Rodrigues, Rodrigo
Abstract: Introduction: Changes in the lower extremities' biomechanics are associated with gluteus medius (GMed) weakness and increased tensor fascia latae (TFL) activation. Objective: To determine which exercises produce greater GMed activity while minimizing TFL activation during the concentric and eccentric phases of three single-joint strengthening exercises. Design: Controlled laboratory study. Setting: Laboratory. Participants: Eleven males (age: 29.18 ± 4.51 years; body mass: 84.01 ± 14.48 kg; height: 1.74 ± 0.07 m; body fat: 16.34 ± 3.33%). Main outcome measures: GMed and TFL activation and activation ratio while performing ten maximal repetitions of three exercises: side-lying hip abduction (SLHA); clamshell (CLAM) and hip abductor machine (HAM). Results: GMed activation was greater than TFL in all exercises in both concentric and eccentric phases. There were no differences in GMed activation between the three exercises in both phases. TFL activation was greater in SLHA compared to HAM and CLAM during both phases. In both concentric and eccentric phases, GMed:TFL ratio was greater in HAM compared to CLAM and SLHA. Conclusions: GMed had increased activation compared to TFL in all analyzed exercises. Considering GMed:TFL ratio, if the goal is to preferentially activate GMed while minimizing TFL activation, the hip abductor machine seems to be the best exercise.